Residual force enhancement after stretch of contracting frog single muscle fibers (The Rockefeller University Press, 1982)
Single fibers from the tibialis anterior muscle of Rana temporaria at 0.8-3.8 degrees C were subjected to long tetani lasting up to 8 s. Stretch of the fiber early in the tetanus caused an enhancement of force above the isometric control level which decayed only slowly and stayed higher throughout the contraction. This residual enhancement was uninfluenced by velocity of stretch and occurred only on the descending limb of the length-tension curve. The absolute magnitude of the effect increased with sarcomere length to a maximum at approximately 2.9 micrometers and then declined. The phenomenon was further characterized by its dependence on the amplitude of stretch. The final force level reached after stretch was usually higher than the isometric force level corresponding to the starting length of the stretch. The possibility that the phenomenon was caused by nonuniformity of sarcomere length along the fiber was examined by (a) laser diffraction studies that showed sarcomere stretch at all locations and (b) studies of 9-10 segments of approximately 0.6-0.7 mm along the entire fiber, which all elongated during stretch. Length-clamped segments showed residual force enhancement after stretch when compared with the tetanus produced by the same segment held at the short length as well as at the long length. It is concluded that residual force enhancement after stretch is a property shown by all individual segments along the fiber.